LAND USE/COVER CHANGE IN RUSSIA WITHIN THE CONTEXT OF GLOBAL CHALLENGES - ELENA MILANOVA (Revue Roumaine de Géographie)
The paper presents the results of a research project on Land Use/Cover Change (LUCC) in Russia in relations with global problems (climate change, environment and biodiversity degradation). The research was carried out at the Faculty of Geography, Moscow State University on the basis of the combination of remote sensing and in-field data of different spatial and temporal resolution. The original methodology of present-day landscape interpretation for land cover change study has been used. In Russia the major driver of land use/land cover change is agriculture. About twenty years ago the reforms of Russian agriculture were started. Agricultural lands in many regions were dramatically impacted by changed management practices, resulted in accelerated erosion and reduced biodiversity. Between the natural factors that shape agriculture in Russia, climate is the most important one. The study of long-term and short-term LUCC dynamics permits the analysis of the present status and trends of evolution of natural and anthropogenic landscapes. A feasibility study had been undertaken for scale-dependent landscapes applicationsand study of land cover dynamics under ongoing changes in Russia